CLINICAL AND PARACLINICAL CHARACTERISTICS OF OCULAR ADNEXAL MARGINAL ZONE B-CELL LYMPHOMA (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the clinical and paraclinical characteristics of patients with ocular adnexal marginal zone B-cell lymphoma (OAL).Methods: A descriptive retrospective and prospective study was conducted on 16 patients aged 18 and older, diagnosed with ocular marginal zone lymphoma via histopathology and immunohistochemistry from January 2023 to October 2023 at Vietnam National Eye Hospital.Results: The mean age was 59,5 ± 8,7 years; the male-to-female ratio was 1,7. The most common reason for admission was self-detected tumor (56,25%). Typical clinical symptoms included palpable mass (87,5%), proptosis (62,5%) and ptosis (25%). The most frequent locations were orbital soft tissue (62,5%) and conjunctiva (50%). Most patients were in the early stage (Ann Arbor stage I: 62,5%; AJCC stage T2: 81,25%). LDH and Beta2M levels were 100% low; 50% of patients had a low IPI score. Immunohistochemistry showed 100% expression of CD20 and 87,5% for BCL2; the mean Ki67 index was low (7,5%).Conclusion: Ocular adnexal marginal zone lymphoma is common in middle-aged individuals, with a male predominance observed in this study. The disease usually presents at an early stage with a favorable prognosis, consistent with the indolent B-cell marginal zone immunohistochemical profile.
Keywords: Ocular adnexal marginal zone lymphoma, clinical, subclinical, immunohistochemistry.